1991
DOI: 10.1177/026553229100800104
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study into the construct validity of a reading comprehension test: triangulation of data sources

Abstract: Recent research in reading comprehension has focused on the processes of reading, while recent thinking in language testing has recognized the impor tance of gathering information on test taking processes as part of construct validation. And while there is a growing body of research on test-taking strate gies in language testing, as well as research into the relationship between item content and item performance, no research to date has attempted to examine the relationships among all three - test taking strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(101 citation statements)
references
References 15 publications
3
96
0
2
Order By: Relevance
“…This is in line with the findings of Weir et al (1990), Anderson et al (1991), Brutten et al (1991), Lumley (1993), Weakly (1993), and Bachman et al (1988 who achieved a sufficient degree of agreement on what are being measured by individual test items, but contrary to the findings of Alderson and Lukmani (1989) and Alderson (1990a) who concluded that judges are not able to agree on assigning particular subskills to individual test items.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This is in line with the findings of Weir et al (1990), Anderson et al (1991), Brutten et al (1991), Lumley (1993), Weakly (1993), and Bachman et al (1988 who achieved a sufficient degree of agreement on what are being measured by individual test items, but contrary to the findings of Alderson and Lukmani (1989) and Alderson (1990a) who concluded that judges are not able to agree on assigning particular subskills to individual test items.…”
Section: Discussionsupporting
confidence: 86%
“…Alderson (2000) cites quantitative studies supporting multi-divisible view such as Carroll (1993), Drum et al (1981), Pollitt et al (1985), and Davey (1988). Qualitative studies against a unitary view of reading include Anderson et al (1991), Bachman et al (1988), Brutten et al (1991), Lumley (1993), Weakly (1993) and Weir et al (1990), as cited by Weir and Porter (1994 ). In support of multi-divisible view of reading, Lumley (1993) argues that it may not be possible to say that reading subskills exist objectively as separate, concrete elements.…”
Section: Introductionmentioning
confidence: 96%
“…Oxford (1990) believes that successful use of strategy highly hinges on learners' flexibility. Moreover, Anderson, Bachman, Perkins, and Cohen (1991) found that there was a relationship between strategy use and question type. They found that learners made use of skimming, paraphrasing, guessing, and elimination when they answered difficult items.…”
Section: Reading Comprehension and Strategymentioning
confidence: 99%
“…McGuire and Yewchuk (1996), for example, studied four gifted upper elementary students with reading problems found that these students used evaluation, paraphrasing, and regulation of metacognitive strategies effectively; however, what they significantly showed was individual differences in using strategies. Anderson, Bachman, Perkins, and Cohen (1991) found that there was a significant relationship among question types, learners' performance on reading test and the reading strategy they used. Elsewhere, O'Malley and Chamot (1990) found out that the nature of learners' strategy use influenced their way they performed in a given task.…”
Section: Introductionmentioning
confidence: 96%
“…Por esta misma razón, es necesario que los instrumentos sean efectivos. De acuerdo a nuestra concepción de la evaluación y en concordancia con diversos autores (Anderson, Bachman, Perkins & Cohen, 1991;Alderson, 2000;Golden & Goldman, 2006), para que un instrumento de evaluación sea efectivo, debe cumplir con dos criterios fundamentales: confiabilidad y validez. El primero se refiere a la consistencia de la medición, es decir, a que los resultados de la aplicación del mismo instrumento de evaluación en diferentes instancias y por diversos evaluadores sean similares.…”
Section: Los Instrumentosunclassified